The PTSD Checklist-Civilian Version: Reliability, Validity, and Factor Structure in a Nonclinical Sample - Conybeare, Daniel; Behar, Evelyn; Solomon, Ari; Newman, Michelle G.; Borkovec, T. D. (Journal of clinical psychology, 2012)
Objectives We examined the reliability, validity, and factor structure of the posttraumatic stress diorder (PTSD) Checklist‐Civilian Version (PCL‐C; Blanchard, Jones‐Alexander, Buckley, & Forneris, 1996) among unselected undergraduate students. Participants Participants were 471 undergraduate students at a large university in the Eastern United States and were not preselected based on trauma history or symptom severity. Results The PCL‐C demonstrated good internal consistency and retest reliability. Compared with alternative measures of PTSD, the PCL‐C showed favorable patterns of convergent and discriminant validity. In contrast to previous research using samples with known trauma exposure, we found support for both 1‐factor and 2‐factor models of PTSD symptoms. Conclusions Overall, the PCL‐C appears to be a valid and reliable measure of PTSD symptoms, even among nonclinical samples, and is superior to some alternative measures of PTSD. The factor structure among nonclinical samples may not reflect each of the PTSD symptom “clusters” (i.e., reexperiencing, avoidance/numbing, and hyperarousal). © 2012 Wiley Periodicals, Inc. J. Clin. Psychol. 00:1–15, 2012.